Pengaruh Metode Demonstrasi Terhadap Hasil Belajar IPA Siswa Di Kelas V SDN Gugus 1 Kec. Sungai Pua Kab. Agam - Febriani, Suci; Zen, Mulyani; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe purpose of the research is to know the effect of demonstration methods on student IPA learning outcomes. The research was a quasi eksperimen design types non-equivalent control group design. The population was all student class V the SDN Gugus 1 Kec. Sungai Pua Kab. Agam. Taking technique of sample was purposive sampling. The sample of this research was student class VA and VB SDN 14  Simpang Ampek. Based on the analisys, obtained tcount>ttable was 3,0138  > 2,0211 with significant level α = 0,05 so it can be conclude Ha accepted  that there is an affect of the demonstration method on the learning outcomes of students in the class V SDN Gugus 1 Kec. Sungai Pua Kab. Agam. Keywords: Demonstration Method, Learning Outcome IPA.